PENGARUH BOOK-TAX DIFFERENCES TERHADAP EARNINGS PERSISTENCE DENGAN KOMPONEN AKRUAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN JASA DI INDONESIA - Anisa Alfiarini; Dul Muid (Diponegoro Journal of Accounting, 2015)
This study aimed to examine the effect of differences between accounting income and taxable income (Book-Tax Differences) against earnings persistence with accrual as a moderating variable component in service companies in Indonesia. Book-tax differences in the present study were divided into three groups: Large Positive Book-Tax Differences, Negative Large Book-Tax Differences and Small Book-Tax Differences which each is used as independent variables. As well as the size of the company contained in this study is used as a control variable to earnings persistence. The data used in this research is secondary data. Data collection techniques with technical documentation. The method used in this study using regression analysis with dummy variables. From the results of the research that has been done, the first and second hyphoteses each have significant value that is <0.05. Neither Large Positive Book-Tax Differences and Negative Large Book-Tax Differences show that there is a significant effect on earnings of lower persistence with accrual as a moderating variable component. Small book-Tax Differences show that there is a positive effect on earnings persistence with accrual as a moderating variable component. As well as the size the companies in the study show that your company size is directly positive effect on the increase in earnings persistence.